From dragon to goose: has the Chinese dragon lost its fire?. (1st January 2012) - Tinker, Tony; Sy, Aida
The state of the world economy is something of a moving feast. Each week, news from the USA, Europe and now China registers a new development, with a growing appreciation of the interconnectedness of the world economy. 'Understandings' are often confounded with 'happy talk' (what used to be called 'ideology') where economic and political actors attempt to manipulate their market standing, agency rating etc., for their own parochial interests. France and England's recent struggles to 'dodge the bullet' of a rating's agency downgrade are a case in point. Happy talk about China is the latest shoe to drop. The West is beginning to realise that the Chinese Dragon is sicker than we realised.